Rehabilitation : A Life's Work - Fang, Harry Sinyang, 1923- (Book collections on Project MUSE., 2002)
This is the autobiography of a remarkable man and his remarkable career. Sir Harry Fang, a world-renowned pioneer in the development of rehabilitation medicine, tells a fascinating story of his own emergence as an expert in medical practice and the emergence of a whole new branch of that practice.